Asia journal of theology - Association for Theological Education in South-East Asia; Northeast Asia Association of Theological Schools (Singapore ATESEA, 2001)
"The Asia Journal of Theology (AJT) is the organ of the Board of Theological Education of the Senate of Serampore College (university) and the Association for Theological Education in South East Asia. The purpose of the journal is to encourage Asian biblical scholarship and theological thinking; to relate the Gospel to our cultural, historical, and religious situation in Asia; to study problems related to the teaching of theology and aims of theological education in Asia; to share news about member schools of the Associations and to maintain contact with theology and ministry beyond the region of Asia. Opinions expressed in the articles, book reviews, etc., are those of the authors and do not necessarily represent the views of the editors"
Keywords: Zeitschrift